Developing Professional Teacher to Improve Madrasah Student Character - Komarudin, Muhammad (Jurnal Pendidikan Islam, 2021)
This study was aimed at investigating research and development (R&D) model applied to Akidah-Akhlak subject teachers in strengthening their students’ character in madrasah in South Jakarta. This research applied R&D using ADDIE version which consisted of: analysis, design, development, implementation, and evaluation. The research subjects were selected purposively involving 30 teachers. The results of the study show that the training model for the teachers was carried out with an emphasis on empowering the teachers’ professionalism. The development program was implemented through training and mentoring based on the modules. The results of the module-based teacher professional development can build the students’ character. The syntax for the training program started from preliminary studies, model descriptions compilation, model development, and professional teacher outcomes (compiling lesson plan, carrying out learning activities, conducting classroom action research). The implementation of the module-based teacher professional development had a significant impact on increasing the teachers’ pedagogic competence. They demonstrated a teaching vision that emphasized the importance of teaching the subject to their students. Teaching and learning activity which is based on the teachers’ professionalism can build students’ positive character in madrasah in South Jakarta.